Neonatal mortality rates at Al-Sadar city 2015 – 2019 - Rasheed, Hiba A; Al Jadiry, Huda; Al-Kaseer, Eman A (Technium BioChemMed, 2022)
Neonatal mortality is an index for newborn care and maternal health care. It is a useful indicator for obstetrical and neonatal healthcare services quality and availability. It is influenced by environmental, economic and social factors. Therefore, it is a measure of socio-economic status and health system. The study was a cross sectional one. It was conducted at Al Resafa side in Baghdad city. The requested data were reviewed from medical records (sex, cause of death, etc.). Chi-square was used to show the impact of dependent variables (death causes) on the independent variables (sex, and type of neonatal death). P value < 0.05 was considered statistically significant. The results showed number of neonatal deaths per 1000 livebirths ranged from 19.30-19.08 per 1000 livebirths between 2015 - 2019 respectively. Males had the highest neonatal deaths through studied years (54.8%, 54.5%, 56.4%, 57.2%, and 59 respectively). Prematurity (487, 32.1%), and respiratory distress syndrome (387, 25.5%) were significantly the common causes of early neonatal deaths. Sepsis (216, 30.1%), and respiratory distress syndrome (149, 20.8%) were significantly the main late neonatal deaths causes (kh 2= 429.582, p value = 0.001). Both males and females mainly died from prematurity (340, 285; 27%, 29.2% respectively). The distribution of causes of neonatal death were significantly varied between sexes (kh2= 20.782, p value= 0.001). In conclusions, neonatal mortality rate is high in the studied period. Two thirds of neonatal death occurred early.